2021
DOI: 10.5489/cuaj.7224
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among caregivers in the era of the COVID-19 pandemic: Insights and challenges

Abstract: The arrival of COVID-19 modified the way we live, care, teach, and self-care tremendously. Indeed, our personal and professional lives were much affected, and despite the fact that Canadian healthcare workers (HCW) and systems had some time to prepare in comparison to other countries, we faced a scenario that resembled no other. Adding the negative effects of a never-before-seen pandemic to the already well-known risk of burnout among HCW could surely increase the likelihood of colleagues, as well as ourselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
1
Order By: Relevance
“…A SB normalmente está associada a alta carga laboral, baixo controle sobre o processo de trabalho e pouco suporte da chefia e de colegas 8 . Além desses aspectos, os efeitos negativos da pandemia de COVID-19 trouxeram novos fatores que podem aumentar o risco de esgotamento nos profissionais de saúde 9,10 . Considerando que esta temática tem sido pouco abordada entre os trabalhadores da saúde indígena, o presente estudo buscou investigar a prevalência da síndrome de burnout (SB) em profissionais de nível superior atuantes na saúde indígena no Brasil e fatores associados.…”
Section: Introductionunclassified
“…A SB normalmente está associada a alta carga laboral, baixo controle sobre o processo de trabalho e pouco suporte da chefia e de colegas 8 . Além desses aspectos, os efeitos negativos da pandemia de COVID-19 trouxeram novos fatores que podem aumentar o risco de esgotamento nos profissionais de saúde 9,10 . Considerando que esta temática tem sido pouco abordada entre os trabalhadores da saúde indígena, o presente estudo buscou investigar a prevalência da síndrome de burnout (SB) em profissionais de nível superior atuantes na saúde indígena no Brasil e fatores associados.…”
Section: Introductionunclassified
“…BS is usually associated with high workload, low control over the work process and little support from management and colleagues 8 . In addition to these aspects, the negative effects of the COVID-19 pandemic have brought new factors that can increase the risk of burnout in health professionals 9,10 . Considering that this issue has been little discussed among indigenous health workers, this study sought to investigate the prevalence of burnout syndrome in higher education professionals working in indigenous health in Brazil and associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the current COVID-19 pandemic poses new challenges to workers from all around the world, from a large variety of work contexts. For example, in healthcare, this pandemic has brought many stressors, such as the risk of infection, isolation, economic concerns, and new responsibilities (Franc-Guimond & Hogues, 2021). A recent systematic review revealed it is difficult to determine the impact of the pandemic on the prevalence of burnout because many healthcare professionals were experiencing these symptoms before the pandemic due to the grueling nature of this field of work (Gualano et al, 2021).…”
Section: Introductionmentioning
confidence: 99%